Age-Friendly Cities Performance Index: proposal of model - Pinheiro, Francisco Alves; Diogo, Miguel Fernando Tato; Góis, Joaquim Eduardo de Souza; Paúl, Constança (Revista Kairós-Gerontologia, 2021)
The aim of this research was to build an index model capable of assessing and monitoring the performance of cities as age-friendly ones. The hierarchy of the variables was determined using the "Hierarchical Process Analysis" technique based on the weight assigned by the social actors in a selected municipality in northern Portugal (Trofa). The "Principal Component Analysis" resulted in the Age-Friendly Cities Performance Index (AgeCPI) model, with 29 indicators validated by the participation of the Local Council of Social Action. This case study, evidence the potentiality of the model for the diagnosis of the municipality status, in relation to all municipalities participating in the research.